Acoustic emission analysis of failure processes in polyethylene and recycled tire rubber blends - Ákos Görbe; Gergő Zsolt Marton; Tamás Bárány (Polymer Testing)
In this study, we developed a test method using acoustic emission (AE) to investigate the failure process and degree of compatibility of low-density polyethylene (LDPE) blends filled with ground tire rubber (GTR). The blends contained 40 wt% of GTR, which is incompatible with the matrix material and altered their fracture behavior significantly. We could define three stages of the tensile curves based on the amplitude of the emitted signals. Furthermore, we demonstrated the effect of compatibilization using ethylene-vinyl-acetate: compatibilization facilitated a stronger interface between the matrix and filler, resulting in signals with higher amplitude. We analyzed the main signal properties and found a shift indicating compatibilization in all of them. We also studied the crack propagation of the specimens using tear tests and found that the incorporation of EVA in LDPE-GTR blends facilitated a more stable crack propagation, as indicated by fewer acoustic events.